Scope for MSME's and Small Businesses growth in the era of Digital India amidst Covid-19 pandemic - A theoretical Review (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The advent of Covid-19 pandemic worldwide forced all the economies around the Globe to adopt the procedures and practices of social distancing and other Covid-19 Protocols. This transformation gave rise to many new businesses like Digital Payment applications, Covid Mask manufacturers, Hand Sanitizer manufacturers (Branded and Local makers), Indian Pharmaceutical Companies, etc. Covid-19 and Digitalisation post Covid, proved to be a boon and bane for many people around the Globe especially the business class which ultimately affectedthe service class also as shutting up and opening up of Businesses led to changes in composition of employment all over. The increasing use of Digital payments, Wallets, This research attempts to theoretically analyse the impact of Digitalisation on MSME’s growth in Indian Economy and scope for their future ahead.
Keywords: MSME; Covid-19; Digital India; Business; Growth